Concept of Fintech and Financial Inclusion in the Light of Sharī`ah - Wan Yusoff, Wan Ahmad Zarif; Mohd Noh, Mohd Shahid; Che Seman, Azizi (Al-Basirah Journal, 2024)
A technology integration that strictly complies with Sharī`ah principles within the financial services industry is known as Islamic fintech. This suggests that financial services that adhere to Sharī`ah principles can be provided via cutting-edge digital channels referred to as omni-channels. By analyzing the secondary sources related to the topic guided with Sharī`ah-based information collected from the jurisprudence books, this paper aims at enlightening the horizon of financial inclusion from Sharī`ah perspective. As a result, fintech principles are upheld by Islamic tenets when they align with principles that support knowledge, innovation, virtuous conduct, human welfare, and considerations for potential harms or suffering to humanity. This is based on evidence from al-Qur’ān, Ḥadīth, Maqāṣid al-Sharī`ah and Ma’ālāt al-Af`āl. The legitimacy of fintech is still intact as long as the above-mentioned requirements are fulfilled.